Discriminative characteristics of marginalised novel psychoactive users: a transnational study - Felvinczi, K.; Benschop, A.; Urbán, R.; Van Hout, M. C.; Dąbrowska, K.; Hearne, E.; Henriques, S.; Kaló, Z.; Kamphausen, G.; Silva, J. P.; Wieczorek, L.; Werse, B.; et al. (International Journal of Mental Health and Addiction, 2020)
New psychoactive substances (NPS) continue to be considered as a major public health concern in many European countries. The study was implemented within the framework of a transnational project of six European countries (Germany, Hungary, Ireland, Netherlands, Poland, Portugal). Our aim here is to report on the distinct and differentiating characteristics of marginalised NPS users. Three subgroups of a total of 3023 adult NPS users (socially marginalised, night life, online community) were examined regarding their sociodemographic haracteristics, substance use, and external motives towards NPS use. Poland and Hungary reported higher rates of NPS use in comparison to traditional controlled drugs.The external/contextual motives did not play a central role in the background of NPS use, the least important motives were alleged legality and non-detectability of these substances. Marginalised (defined as those accessing low threshold harm reduction services) users’ substance use patterns are different from the other two groups in terms of showing more intense and riskier drug use. The most important variables which contributed to be categorised as a marginalised NPS user were lower level education, being older, having an unfavourable labour market position and using drugs intravenously. Contextual motives did not play a decisive role in being categorised as a marginalised user when drug use pattern was controlled. These identified discriminative features of marginalised drug users should inform policy makers to develop and implement tailor-made interventions targeting this user group to successfully tackle the elevated public health concerns associated with NPS use.